The Study on Instructional Guideline to Enhance Active Citizenship for Grade 6 Students at Photsri Municipal School, Under the Administration of Mahasarakham Municipality - Shaisombat, Jaturapat; Wongsaphan, Montree (Journal of Education Rajabhat Maha Sarakham University, 2024)
This study had two goals: 1) to study components for being active citizenship and 2) to study instructional guideline to enhance active citizenship for Grade 6 students at Pho Si Municipal School, under the administration of Mahasarakham Municipality. The Research were conducted in two phases, Phase 1 documents synthesizing and Phase 2 study empirical data. The key informants in Phase 2 were two teachers of Pho Si Municipal School, purposive selected form their expertise with a strong background in teaching active citizen subject. The research instruments included data recording forms and instruction interview forms. The research revealed four components of being a strong citizen, which include: 1) respecting rights, 2) being responsible for roles and duties, 3) engaging in critical participation, and 4) being an agent of change. The instruction to enhance active citizenship among Grade 6 students at Pho Si Municipal School, under the Mahasarakham Municipality should emphasize on learner-centered incorporating active learning that allows students to engage in real-world situations and foster respect for rights, adherence to rules, responsibility for roles and duties, critical thinking in logic analyzing information, and promote of democratic values among the students.